Sosialisasi Strategi Branding dan Peningkatan Kinerja Karyawan Untuk Meningkatkan Minat Beli Pelanggan - Army Cahya Putra Rustamaji; Novi Fitria Hermiati; Daspar Daspar; Isarianto Isarianto; Arif Widodo Nugroho (Lembaga Pengembangan Kinerja Dosen, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are very important to the Indonesian Economy, but often MSMEs face problems in terms of marketing and management. In an effort to increase consumer buying interest, this Service Activity investigates effective marketing, branding, and employee performance strategies for MSMEs. Cheesecuit Micro, Small, and Medium Enterprises (MSMEs) face key challenges related to marketing, branding, and performance that can impact consumer awareness and interest in purchasing products. This service identifies factors that influence consumer buying interest and analyzes what marketing, branding, and management strategies are appropriate to increase consumer buying interest for cheesecuit businesses. The proposed solutions include building an integrated marketing strategy, utilizing digital marketing, improving product quality, building partnerships and distribution networks, training and mentoring for MSMEs, as well as improving Resource Management in improving employee performance. This service activity is expected to have a positive impact on business actors in order to increase consumer purchasing power and provide benefits for business owners.